Waste Water Recovery System with Heat Pump for Hot Water Preparation. (June 2019) - Červín, R; Matuška, T
Abstract: Waste water heat recovery is currently one of the possible ways how to reduce energy performance of buildings. The mathematical model using specific heat pump parameters is presented in this article. The aim was to verify efficiency of the waste water recovery system with heat pump for domestic hot water heating in family houses. The model enabled to evaluate heat recovery effectiveness during a day cycle. The first set of simulations of a typical day cycle has shown that the heat pump with recuperation of waste water is not effective solution for family houses. However, it might be interesting for the objects with larger consumptions. Another simulations for these objects were performed and more promising results were reached.